The Effectiveness of Flashcard Media and Letter Learning Applications to Help Dyslexic Children's Reading Ability in Elementary School - Syifa Mutiara Puradireja (Universitas Nahdlatul Ulama Surabaya, 2022)
Reading is one of the most important skills and is often taught in elementary schools. Usually learning difficulties that are often found are reading difficulties (dyslexia). This article tries to explore the characteristics of the difficulties experienced by dyslexic students in the reading process at school, as well as efforts to overcome reading difficulties for dyslexic students in elementary schools through flashcard media and the 'Learn Letters' application on smartphones. The researcher uses a qualitative type of research with a case study method. The subject of the study was a 7-year-old dyslexic child with the initials APS who attended one of the public elementary schools in the city of Bogor. Data collection techniques used are observation, interviews, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Research findings show that APS can memorize all the letters of the alphabet, but cannot distinguish the letters [b] and [d], [m] and [n], and has difficulty writing some letters and numbers correctly. The results showed that the flashcard learning media and the 'Learning Letters' application could improve the reading skills experienced by the research subjects. Recommendations from research results on the effectiveness of the flashcard creative learning media method and the 'Learning Letters' application can be followed up by using other applications or more interesting media by utilizing digital technology